Incidence des fluctuations climatiques sur la taille du renne (Rangifer tarandus) au Pléistocène supérieur - Magniez, Pierre (Quaternaire, 2010)
Current ecological studies show that the ungulate populations undergo the effects of climatic oscillations through the combination of intrinsic and extrinsic factors. Furthermore, the close relationship between body size and environment has been discussed for several years. This led to the elaboration of general laws such as that of the well-known and discussed Bergmann (1847) and Allen (1877) laws describing the phenomenon. As far as the archaeological context is concerned, different authors suggested explicative patterns of the osteometrical variability observed on the reindeer. Recently, Weinstock synthesised reindeer body size evolution and its geographical variability in Central and Western Europe during the Late Pleistocene. The author insists on the multivariate character of the causes. In the present study, several South-western French sites are studied in order to obtain a diachronic vision of the Late Pleistocene within a regional scale. A well known methodology is used (apply of size index: V.S.I. for Variability Size Index). Significant differences in reindeer body size estimation were found at OIS 4, 3 and 2. According to faunal, palynological and sedimentological data, it seems that the climate played an important role in body size changes, highlighting great phenotypic plasticity in Late Pleistocene reindeer. Particularly, female body size showed greater variation than males. However, our study also shows that data concerning the population structure, and particularly the sex ratio and the sexual dimorphism, must be taken into account. Les études écologiques actuelles montrent que les populations d’ongulés subissent les effets des oscillations climatiques par le biais combiné de facteurs intrinsèques et extrinsèques. La relation plus ou moins fine liant la taille corporelle et l’environnement est par ailleurs débattue depuis de nombreuses années, tant et si bien qu’il existe des lois à portée générale décrivant le phénomène comme celles bien connues (et discutées) de Bergmann (1847) et d’Allen ...